Sparse identification of time-space coupled distributed dynamic load. (1st February 2021) - Liu, Jie; Li, Kun
Highlights: Propose a novel sparse identification method for distributed dynamic load. The time-space coupled load is decoupled by proper orthogonal decomposition. Blind source separation is adopted to realize load time history identification. Orthogonal matching pursuit is employed to achieve the sparse representation of load distribution function. The time-space coupled load is equivalent to several concentrated dynamic loads. Abstract: A novel and efficient method utilizing blind source separation and orthogonal matching pursuit is proposed in this paper to identify the time-space coupled distributed dynamic loads. By using proper orthogonal decomposition, the time-space coupled distributed dynamic load can be decomposed into the form of series of independent spatial distribution functions and time history functions. Considering the influences of the load distribution functions and time history functions on the structural responses are different, the non-uniqueness of distributed dynamic load identification is analyzed. The modal loads can be regarded as the weighted mixtures of the unknown independent time history functions and are identified by Green's kernel function method and regularization. Then, the blind source separation technique is introduced to realize the identification of load time history functions, and the orthogonal matching pursuit algorithm is adopted to achieve the unique sparse solutions for load distribution functions. Finally, the distributed dynamic load is sparsely identified and equivalently represented as several concentrated dynamic loads acting on the appropriate positions. This proposed method is capable to deal with the time-space coupled distributed dynamic load on complicated structures, and to realize its spatial distribution representation and time history reconstruction separately. The results of the numerical examples demonstrate the reasonability and effectiveness of the method.